Investigation of Ebolavirus exposure in pigs presented for slaughter in Uganda - Atherstone, Christine; Diederich, S.; Pickering, B.; Smith, G.; Casey, G.; Fischer, K.; Ward, M.P.; Ndoboli, D.; Weingartl, H.; Alonso, Silvia; Dhand, N.; Roesel, Kristina; et al. (Hindawi Limited, 2021)
In 2008, an outbreak of Reston ebolavirus (RESTV) in pigs in the Philippines expanded our understanding of the host range of ebolaviruses. Subsequent experimental infections with the human‐pathogenic species Zaire ebolavirus (EBOV) confirmed that pigs are susceptible to African species of ebolaviruses. Pig keeping has become an increasingly important livelihood strategy throughout parts of sub‐Saharan Africa, driven by increasing demand for pork. The growth in pig keeping is particularly rapid in Uganda, which has the highest per capita pork consumption in East Africa and a history of sporadic human outbreaks of Ebola virus disease (EVD). Using a systematic sampling protocol, we collected sera from 658 pigs presented for slaughter in Uganda between December 2015 and October 2016. Forty‐six pigs (7%) were seropositive based on ELISA tests at two different institutions. Seropositive pigs had antibodies that bound to Sudan NP (n = 27), Zaire NP (Kikwit; n = 8) or both NPs (n = 11). Sera from 4 of the ELISA‐positive pigs reacted in Western blot (EBOV NP = 1; RESTV NP = 2; both NPs = 2), and one sample had full neutralizing antibody against Sudan ebolavirus (SUDV) in virus neutralization tests. Pigs sampled in June 2016 were significantly more likely to be seropositive than pigs sampled in October 2016 (p = .03). Seropositive pigs were sourced from all regions except Western region. These observed temporal and spatial variations are suggestive of multiple introductions of ebolaviruses into the pig population in Uganda. This is the first report of exposure of pigs in Uganda to ebolaviruses and the first to employ systematic abattoir sampling for ebolavirus surveillance during a non‐outbreak period. Future studies will be necessary to further define the role pigs play (if any) in ebolavirus maintenance and transmission so that potential risks can be mitigated.